Transparency and deliberation within the FOMC: a computational linguistics approach - Hansen, S; McMahon, M; Prat, A (Oxford University Press, 2017)
How does transparency, a key feature of central bank design, affect monetary policymakers’ deliberations? Theory predicts a positive discipline effect and negative conformity effect. We empirically explore these effects using a natural experiment in the Federal Open Market Committee in 1993 and computational linguistics algorithms. We first find large changes in communication patterns after transparency. We then propose a difference-in-differences approach inspired by the career concerns literature, and find evidence for both effects. Finally, we construct an influence measure that suggests the discipline effect dominates.